EDUKASI STRATEGI BAURAN PROMOSI UMKM UD KREASI LUTVI - Lambok Manurung; Etty Harya Ningsi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
A company must always stay updated and creative to remain competitive with other businesses that release similar and substitute products. This requires management that can effectively manage the business. It's important to retain existing consumers or customers and prevent them from switching to other businesses. Companies are required to better understand all the needs and desires of consumers and must be able to create products that meet those needs. Additionally, good marketing is also necessary. Effective marketing can increase sales and capture market share. When this is achieved, the company can ensure maximum profit. However, if the marketing efforts are incorrect or insufficient, it will result in decreased sales, impacting the company's revenue. To increase market share, companies need to implement competitive strategies using the Promotion Mix Strategy. This strategy is used by companies to understand the strengths, weaknesses, opportunities, and threats they face to increase market share and attract more customers, as customers are the lifeblood of any company. This is essential due to the intense competition among companies in the same industry, prompting business owners to devise strategies that can increase their market share and attract more customers to ensure the company's sustainability. Based on the results of the SWOT analysis, the promotion mix strategy can be applied at UD. Kreasi Lutvi includes: building partnerships with online agents, prioritizing electronic advertising media, expanding market share, improving product quality, and enhancing the quality of human resources in the Marketing field. Keywords: Customer, Increase, Promosi, Strategi,